Perlindungan Hukum Bagi Konsumen Belanja Online Dikaitkan Dengan Undang-Undang Nomor 8 Tahun 1999 dan Undang-Undang Nomor 11 Tahun 2008 - Leny Melinda (Universitas Jayabaya, 2015)
The phenomenon of trafficking through the Internet is only one form of behav ioral change caused by the information technology revolution in the midst of society. Such conditions on the one hand is very beneficial to the interests of consumers because of their need for goods and /or services desired can be met as well as more wide open freedom to choose different types of quality of goods and/or services according to their abilities. Normative juridical research method that is legal research done by researching library materials or secondary data as the base material to be tested by conducting a search for rules and literature relating to the cases studied. The results showed Law No. 8 of 1999 on Consumer Protection strongly emphasizes that such rules can only apply to businesses engaged in the legal territory of the Republic of Indonesia. To support the legal protection of the perpetrators of the transaction online, the existence of Law Number 11 Year 2008 on Information and Electronic Transactions made partner law Protection Act consumer to support each other.